Age Related Histomorphological Studies on Olfactory Bulb of Pig (Sus scrofa) - Sujana, K.M. Sujana (Indian Journal of Veterinary Anatomy, 2019)
The histomorphological aspects of Olfactory bulb were studied in Large White Yorkshire cross-bred pigs at different age groups. The Olfactory bulb was composed of six layers; the olfactory nerve layer, the glomerular layer, the external plexiform layer, the mitral cell layer, the internal plexiform layer and the granule cell layer from outside to inside. The olfactory nerve layer was thick and consisted mostly of horizontally oriented bundles of nerve fibers. The glomerular layer contained many glomeruli of various sizes of which the large sized glomeruli were predominant in grower and finisher age groups. The mitral cell layer consisted of many mitral cells, few tufted and granule cells. The mitral cell density was decreased, whereas size of mitral cells increased with agefrom preweaner to finisher age groups. The granular layer was the predominant layer of the paleocortex and contained granule cells. The olfactory nerve layer, the glomerular layer and the granule cell layers were predominantly thick in finisher pigs when compared to preweaner and grower pigs.